Reducing the risk of major elective surgery: randomised controlled trial of preoperative optimisation of oxygen delivery. Issue 7191 (24th April 1999) - Wilson, Jonathan; Woods, Ian; Fawcett, Jayne; Whall, Rebecca; Dibb, Wendy; Morris, Chris; McManus, Elizabeth
Abstract: Objectives: To determine whether preoperative optimisation of oxygen delivery improves outcome after major elective surgery, and to determine whether the inotropes, adrenaline and dopexamine, used to enhance oxygen delivery influence outcome. Design: Randomised controlled trial with double blinding between inotrope groups. Setting: York District Hospital, England. Subjects: 138 patients undergoing major elective surgery who were at risk of developing postoperative complications either because of the surgery or the presence of coexistent medical conditions. Interventions: Patients were randomised into three groups. Two groups received invasive haemodynamic monitoring, fluidand either adrenaline or dopexamine to increase oxygen delivery.Inotropic support was continued during surgery and for at least12 hours afterwards. The third group (control) received routine perioperative care. Main outcome measures: Hospital mortality and morbidity. Results: Overall, 3/92 (3%) preoptimised patients died compared with 8/46 controls (17%) (P=0.007). There were no differences in mortality between the treatment groups, but 14/46 (30%)patients in the dopexamine group developed complications compared with 24/46 (52%) patients in the adrenaline group (difference 22%, 95%confidence interval 2% to 41%) and 28 patients (61%) in the control group (31%, 11% to 50%). The use of dopexamine was associated with a decreased length of stay in hospital. Conclusion: Routine preoperative optimisation of patients undergoing major elective surgery would be a significant and cost effective improvement in perioperative care.